Reducing mid-air collision risk in controlled airspace: lessons from hazardous incidents - Brooker, Peter (Elsevier, 2005)
The collection and analysis data on hazardous air traffic management (ATM) incidents is an important task. Expert judgement about such incidents needs to be carried out within a systematic and consistent safety framework. The mark of the genuine safety expert is to be able to ask the right questions concerning potential accidents. Hazards and risks are not ‘facts’ or ‘events’ that ‘exist’, but rather judgements made about conditional futures and their consequences. A hazardous situation is one in which the outcome was not ‘system controlled’, with some potential outcomes having significant negative consequences. System controls in this sense cover all the means by which the system is held stable (=defended) against the potential negative consequences. The ATM system can be (over-) simplified to consist of three structural system layers acting as the system controls: Planning (pre-operational), Operation (the flight in progress), and Alert (the ground and air protection enabled by conflict alert systems, on which the controller/pilot will act). A hazardous event is one in which a high degree of conflict between aircraft is observed plus a low confidence that the remaining system layers would generally provide the necessary corrective action.
Keywords: Collision risk; Air traffic control; Incidents